2017
DOI: 10.1103/physrevd.95.094513
|View full text |Cite
|
Sign up to set email alerts
|

Precise determination of the three-quark potential in SU(3) lattice gauge theory

Abstract: We investigate the static interquark potential for the three-quark system in SU(3) lattice gauge theory at zero temperature by using Monte Carlo simulations. We extract the potential from the correlation function of the three Polyakov loops, which are computed by employing the multilevel algorithm. We obtain remarkably clean results of the three-quark potential for O(200) sets of the three-quark geometries including not only the cases that three quarks are put at the vertices of acute, right, and obtuse triang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 51 publications
6
43
0
Order By: Relevance
“…1 contain strikingly different shapes: whereas most of Ref. [5] points (triangle shapes) lie outside of the three straight lines in Fig. 1, defined by the right-triangle configurations, most of Ref.…”
Section: Hyper-spherical Coordinatesmentioning
confidence: 96%
See 2 more Smart Citations
“…1 contain strikingly different shapes: whereas most of Ref. [5] points (triangle shapes) lie outside of the three straight lines in Fig. 1, defined by the right-triangle configurations, most of Ref.…”
Section: Hyper-spherical Coordinatesmentioning
confidence: 96%
“…The lattice data from Refs. [4,5] were converted into permutation-adapted hyper-spherical coordinates by the above equations. We plotted those data points in the x-y projection of the shape sphere.…”
Section: Hyper-spherical Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] "finds support for the ∆ Ansatz", whereas the most recent Ref. [24] finds that "The potentials of triangle geometries are clearly different from the half of the sum of the two-body quark-antiquark potential", i.e., suggesting that is not the ∆ Ansatz. All of which indicates that the lattice QCD potential is neither pure Y Ansatz, nor a pure ∆ Ansatz.…”
Section: Three-body Spin-independent Potentialsmentioning
confidence: 98%
“…for heavy sources has been addressed on the lattice in several works [41][42][43], where it has actually been found that up to numerical uncertainties the potential is linearly rising, and the corresponding string tension is numerically identical to the one of the qq system (see specifically Ref. [43]). In this section we show analytically that under very specific assumptions this must actually be true.…”
Section: Quark-diquark Potential From Polyakov Loop Correlatorsmentioning
confidence: 99%